2022
DOI: 10.21203/rs.3.rs-2114141/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tumor to liver maximum standardized uptake value ratio of FDG-PET/CT parametersBBpredicts tumor treatment response and survival of stage III non-small cell lung cancer

Abstract: Bacground: To assess the predictive values of primary tumor FDG uptake for patients with inoperable stage III non-small cell lung cancer (NSCLC) after concurrent chemoradiotherapy (CCRT). Methods: A total of 107 patients with diagnosis of stage III NSCLC and CCRT were enrolled in this study. The tumor maximum uptake value (SUVmax) was standardized by calculating several ratios between tumor and each background tissues. The receiver operating characteristics curve (ROC) was used to compare the predictive power… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Although pretreatment lymph node SUVmax as a sole parameter has been shown to be a signi cant prognosticator in various cancer types(8, 9, 27-31), there are some well-known drawbacks of using nonnormalized SUV, e.g., partial volume effect, uptake time dependence of the SUV, and interstudy variability of image acquisition and reconstruction parameters, which could possibly undermine the reliability of the SUVmax values (12,(32)(33)(34). The strength of NTR is that by normalizing the lymph node SUVmax to the primary tumor SUVmax, NTR may be less susceptible to the inter-scanner variability, and may have better generalizability (20,(35)(36)(37)(38)(39)(40)(41). In a study on esophageal squamous cell carcinoma patients, Lin et al assessed the potential impact of employing different PET/CT scanners on the NTR and lymph node SUVmax, and demonstrated that the variation of the optimal cutoff values and the interquartile range of the NTR obtained by the two different PET/CT scanners was minimal, while the non-normalized lymph node SUVmax suffered signi cantly greater inter-scanner variability (20).…”
Section: Discussionmentioning
confidence: 99%
“…Although pretreatment lymph node SUVmax as a sole parameter has been shown to be a signi cant prognosticator in various cancer types(8, 9, 27-31), there are some well-known drawbacks of using nonnormalized SUV, e.g., partial volume effect, uptake time dependence of the SUV, and interstudy variability of image acquisition and reconstruction parameters, which could possibly undermine the reliability of the SUVmax values (12,(32)(33)(34). The strength of NTR is that by normalizing the lymph node SUVmax to the primary tumor SUVmax, NTR may be less susceptible to the inter-scanner variability, and may have better generalizability (20,(35)(36)(37)(38)(39)(40)(41). In a study on esophageal squamous cell carcinoma patients, Lin et al assessed the potential impact of employing different PET/CT scanners on the NTR and lymph node SUVmax, and demonstrated that the variation of the optimal cutoff values and the interquartile range of the NTR obtained by the two different PET/CT scanners was minimal, while the non-normalized lymph node SUVmax suffered signi cantly greater inter-scanner variability (20).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, early prediction of the treatment process is crucial. Many studies evaluating BM/L in patients with non-SCLC have reported that PFS and OS were worse in patients with BM/L > 1 [21,[29][30][31][32]. However, there are no studies evaluating these parameters in patients with LD-SCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, early prediction of the treatment process is crucial. Many studies evaluating BM/L in patients with non-SCLC have reported that PFS and OS were worse in patients with BM/L > 1 [21,29–32].…”
Section: Discussionmentioning
confidence: 99%